HUBUNGAN PERAN KELUARGA DALAM MERAWAT LANSIA DENGAN TINGKAT DEPRESI LANSIA DI WILAYAH KERJA PUSKESMAS KUMUN - azma aulia (Jurnal Vokasi Keperawatan (JVK), 2021)
Lack of family role in caring elderly with depression level of elderly marked by still many elderly who less get care from family. The purpose of this study was to determine the role of the family in caring for the elderly against the level of elderly depression in the work area of Kumun Public Health Center in 2015. This type of research is descriptive analytics using Cross Sectional approach. The population in this study were all Elderly who experienced Depression in Working Area of Public Health Center of Kumun with number of 105 people. The sample in this research is 60 respondents. Sampling is done by Accidental Sampling method by taking case or respondent that happened to exist or available somewhere in accordance with research context. The data were collected by using questionnaires and guided interviews in August 2018. The data analysis technique used in this research is Spearman Rank correlation test with 95% confidence degree (? = 0,05).  The results showed that Odd Ratio (OR) = 6.732 with P value = 0,005 where p < 0,05 then H0 rejected and H1 accepted which means that there is a significant relationship between the level of elderly depression with the role of family in caring elderly in the working area of Public Health Center of Kumun. This research is expected to serve as input for Public Health Center to improve nursing service of soul and family to give role and support in elderly care to prevent relapse of depression client.